THE ROLE OF FAITH-BASED ORGANIZING IN HEALTH CARE - Danish Zaidi (European Scientific Journal, ESJ, 2015)
This paper seeks to explore the cross-section of religion and public health. First, I explore the way in which certain religious principles correlate with some moral and philosophical reasons promoting public health. Here, I seek to answer whether or not a case can be made for social justice in global health. I specifically look at the ideas proposed by Norman Daniels and responses to those ideas by other public health theorists. In the second part of the paper, I explore the role that religious and faith-based partnerships can play in the delivery of health care (specifically in underserved rural and urban areas). Here, I argue that religious and faith-based grassroots organizations are: (1) the most prevalent, well connected, and efficient grassroots organizations in underserved areas; (2) have the infrastructure in place for the government to use for health care delivery; (3) are excellent avenues, to advocate for certain preventative health measures. I also present a case study that further illuminates the idea of health care delivery through religious and faith-based organizations. The case explores the story of a faith-based initiative in Bronx that targeted HIV/AIDS prevention. This outreach in Bronx presents two different uses of faith-based organizations: using already-present grassroots infrastructure for health care delivery, but also for preventative health education. Ultimately, this paper seeks to promote the idea of governments and health care practitioners delivering health care – and initiating conversations regarding health – through the infrastructure in place by religious and faith-based organizations.